Challenges and Prospects of Photocatalytic Applications Utilizing Semiconductor Nanocrystals - Moroz, Pavel; Boddy, Anthony; Zamkov, Mikhail (Frontiers in Chemistry, 2018)
Photocatalytic systems based on colloidal semiconductor nanocrystals have gained considerable attention owing to potential benefits that include a visible-range light extinction and a low spatial overlap of photoinduced charges. When coupled to metal catalysts, nanocrystal sensitizers have demonstrated a compelling performance in homogenous photoreduction reactions, including the degradation of organic dyes and hydrogen generation. Going beyond half-cycle reactions, however, the progress in the field of nanocrystal photocatalysis has been rather limited. Here, we review some of the challenges associated with photocatalytic applications of colloidal semiconductor nanocrystals and highlight possible directions aimed towards their resolution. A particular emphasis was made on new paradigms in this field, including the possibility of harvesting triplet excitons and utilizing nanocrystal assemblies to accumulate multiple charges at the reaction site.